An Analysis Students’ Difficulties in Using Present Tense in SMAN 7 Enrekang - Darmijaya, Darmijaya (Majesty Journal, 2022)
This research aims to determine the difficulties that students face in using present tense. This research uses a quantitative descriptive method using tests and interviews. A total of 28 students were selected as samples by random sampling method. Based on the findings of the research, the researcher put the conclusion that the students of SMAN 7 Enrekang still find it difficult to understand tenses, especially the present tense. This is evidenced by an in-depth analysis of the results of student answers that the students mostly made error in omission and then it was followed by addition, misinformation and mis-ordering. The students made errors categorized 133 in omission (34,2%), 107 in addition (27,5%), 61 in mis-information and (15,6%) and 88 in mis-ordering (22,7%). Based on interview, there were three difficulties faced by student in using present tense. The problems faced by student was the form of present tense with percentage 46%, spelling with percentage 32%, and the use of auxiliary with percentage 22%.